2021
DOI: 10.3390/v13081641
|View full text |Cite
|
Sign up to set email alerts
|

Tree Shrew as an Emerging Small Animal Model for Human Viral Infection: A Recent Overview

Abstract: Viral infection is a global public health threat causing millions of deaths. A suitable small animal model is essential for viral pathogenesis and host response studies that could be used in antiviral and vaccine development. The tree shrew (Tupaia belangeri or Tupaia belangeri chinenesis), a squirrel-like non-primate small mammal in the Tupaiidae family, has been reported to be susceptible to important human viral pathogens, including hepatitis viruses (e.g., HBV, HCV), respiratory viruses (influenza viruses,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…We observed that AAV2-WJ11/Cas9 significantly inhibited HBV DNA replication and reduced cccDNA levels both in vitro and in vivo (Kayesh et al, 2020); however, the effect required high multiplicity of genome (MOG) copies of the AAV2 vector, suggesting low transduction efficiency of the AAV2 vector. Using an immunocompetent tree shrew model of HBV infection (Kayesh et al, 2021), we observed a much lower transduction efficiency of the AAV2 vector in liver tissues (unpublished data) than in humanized chimeric mice (Kayesh et al, 2020). Stone et al demonstrated the antiviral efficacy of SaCas9 in humanized FRG mice chronically infected with HBV genotype C, which resulted in decreased total liver HBV DNA and cccDNA levels (Stone et al, 2021).…”
Section: Adeno-associated Virus Vector-based Delivery Of Clustered Re...mentioning
confidence: 77%
“…We observed that AAV2-WJ11/Cas9 significantly inhibited HBV DNA replication and reduced cccDNA levels both in vitro and in vivo (Kayesh et al, 2020); however, the effect required high multiplicity of genome (MOG) copies of the AAV2 vector, suggesting low transduction efficiency of the AAV2 vector. Using an immunocompetent tree shrew model of HBV infection (Kayesh et al, 2021), we observed a much lower transduction efficiency of the AAV2 vector in liver tissues (unpublished data) than in humanized chimeric mice (Kayesh et al, 2020). Stone et al demonstrated the antiviral efficacy of SaCas9 in humanized FRG mice chronically infected with HBV genotype C, which resulted in decreased total liver HBV DNA and cccDNA levels (Stone et al, 2021).…”
Section: Adeno-associated Virus Vector-based Delivery Of Clustered Re...mentioning
confidence: 77%
“…The discovery of NTCP as HBV entry receptor has meanwhile allowed to engineer NTCP-expressing HepG2 cells that are susceptible to HBV infection, albeit infection efficiency is very limited, with no net amplification of the input virus. There are also no convenient small animal models for infection with human HBV; in vivo infection of tree shrews is inefficient [ 207 ] and mice, by necessity immunodeficient, need to be xenotransplanted with human hepatocytes to become susceptible. Improvements are under way on various levels [ 208 , 209 , 210 ] but not yet widely available.…”
Section: Targeting Hbv Capsid Dynamicsmentioning
confidence: 99%
“…For tree shrew infection experiments, the SARS-CoV-2 strain was usually inoculated by oral, intranasal and intraocular routes ( Xu L. et al, 2020 ; Zhao et al, 2020 ; Kayesh et al, 2021 ). After infection, viral RNA was detected in different organs and tissues (e. g. conjunctiva, kidney, bladder, small intestine, testis and ovary) of adult tree shrews, and the peak of viral RNA in lung tissues appeared at day 3 post-infection.…”
Section: Mammal Modelsmentioning
confidence: 99%
“…Additionally, the virus exudation and replication levels were relatively low in tree shrews (6–12 months old), adult tree shrews (2–4 years old) and aged tree shrews (5–7 years old). According to the comparison of the two studies ( Zhao et al, 2020 ; Kayesh et al, 2021 ), the different concentrations of injected virus and the different routes of infection led to above differences, which need further study to clarify. Notably, young tree shrews did not experience a significant increase in body temperature for 6 days after inoculation, but virus shedding was detected from the nose, throat, anus and serum.…”
Section: Mammal Modelsmentioning
confidence: 99%